129 Xe NMR of xenon trapped in fully dehydrated mesoporous silica - Hattori, Mineyuki; Hayamizu, Kikuko; Hiraga, Takashi; Hata, Nobuhiro (Diffusion Fundamentals, 2009)
129Xe NMR spectra of natural abundant xenon gas trapped in fully dehydrated mesoporous materials with pore sizes smaller than 2 nm in diameter were observed under atmospheric pressure in the temperature range between 168 and 373 K. The average pore diameters of the materials studied in this paper were 0.5, 1 and about 2 nm for molecular sieves 5A and 13X and synthesized mesoporous silica, respectively. The samples were fully dehydrated using an ultra-high vacuum (UHV) system and xenon gas was introduced with the sample pre-cooled to 168 K just above the boiling point of xenon. The 129Xe NMR spectra were observed as a function of increasing temperature and the 129Xe shift were observed at each temperature for the three samples under atmospheric pressure. The behaviors of xenon atoms in small pores observed in equilibrium states can provide important information on relationships between the pore structure and 129Xe chemical shift.